From Materials to Structures: Advancement Through Innovation 2012
DOI: 10.1201/b15320-24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentric load on retrofitted reinforced concrete columns confined with FRP

Abstract: Different behaviour of diverse sections of confined Reinforced Concrete (RC) columns under eccentric load is investigated in this study. Three types of sections are considered, which include square columns, square with rounded corners and modified circular columns. Twelve reinforced square concrete columns were made from normal strength concrete and subdivided into four groups. The first three columns were the Reference Group and had no modification.The next three columns were modified with round corners and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The calculated peak loads were close to the experimental peak loads but on the un-conservative side (calculated load higher than experimental load). Pham et al (2013) reported a reduction in the confinement effect by 40% when the eccentricity was increased from zero to 25 mm ( ⁄ of the specimen's thickness). Due to the lack of data of PVC encased walls, the confinement effect of the PVC was approximately estimated to increase the axial load capacity by 10% at all eccentricities.…”
Section: Comparison Between the Experimental And Calculated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculated peak loads were close to the experimental peak loads but on the un-conservative side (calculated load higher than experimental load). Pham et al (2013) reported a reduction in the confinement effect by 40% when the eccentricity was increased from zero to 25 mm ( ⁄ of the specimen's thickness). Due to the lack of data of PVC encased walls, the confinement effect of the PVC was approximately estimated to increase the axial load capacity by 10% at all eccentricities.…”
Section: Comparison Between the Experimental And Calculated Resultsmentioning
confidence: 99%
“…They reported that this particular configuration increased the axial load capacity (confinement effect of the PVC system) by 23% to 25% over the control specimens. On the other hand, for eccentrically loaded columns, Pham et al (2013) reported that the confinement effect decreased as the eccentricity increased for reinforced concrete columns wrapped with fiber reinforced polymer (FRP) sheets. The FRP wraps increased the axial capacity for the concentrically loaded columns by 200 to 400%…”
Section: Comparison Between the Experimental And Calculated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a few publications that analyze nonlinear strain of plates with due regard to the combined effect of initial deflection, physical and geometric nonlinearity and temperature-dependent changes in mechanical properties [3,4,11]. Therefore, this issue needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…A. G. Tamrazyan and A. S. Kozhanova [4] demonstrated high-temperature effects on thermal creep of shallow reinforced concrete shells and flat plates. Pham T. M., et al [11] investigated the influence of eccentric loading on the load-bearing capacity of reinforced concrete columns. Zhang Y. and Karr D. G. [12] developed analytical models to design plates under quasi-static pressure.…”
Section: Introductionmentioning
confidence: 99%